2007
DOI: 10.1111/j.1399-5618.2007.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Cotard's syndrome in adolescents and young adults is associated with an increased risk of bipolar disorder

Abstract: Young people with CS should be monitored carefully for the onset of BD, and families should be educated about this risk. Treatment with mood stabilizers can be helpful for those who develop BD. Within BD associated with CS, early versus late onset should be distinguished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
1
18
0
3
Order By: Relevance
“…Depressive episodes were the most frequent diagnoses in past psychiatric history (42.2%). This is not surprising as it had been reported that 20-30% of depressed children, particularly those with psychosis, a family history of BD and/or pharmacologically induced mania, eventually develop BD [17,22,51,52,57]. Interestingly, 16% had a previous history of brief psychotic episode, indicating that in youth first episode of bipolarity may be non-specific to mood disorders.…”
Section: Discussion J Limitations and Strengthsmentioning
confidence: 89%
See 1 more Smart Citation
“…Depressive episodes were the most frequent diagnoses in past psychiatric history (42.2%). This is not surprising as it had been reported that 20-30% of depressed children, particularly those with psychosis, a family history of BD and/or pharmacologically induced mania, eventually develop BD [17,22,51,52,57]. Interestingly, 16% had a previous history of brief psychotic episode, indicating that in youth first episode of bipolarity may be non-specific to mood disorders.…”
Section: Discussion J Limitations and Strengthsmentioning
confidence: 89%
“…The sample was composed of 45 females and 35 males with a mean age of 15.7 (±1.9) years (range [12][13][14][15][16][17][18][19]. The socio-demographic and clinical characteristics of the sample are summarized in Table 1.…”
Section: J Statistical Analysismentioning
confidence: 99%
“…There is insufficient data about the prevalence and incidence of the syndrome (14). CS is described as a cluster of symptoms as part of an underlying disorder, mostly depressive and bipolar (15)(16)(17)(18). Although our initial diagnosis was major depressive disorder with psychotic features, patients must be followed closely for bipolar disorder because of manic symptoms after treatment with escitalopram, and an increased risk of bipolar disorder during adolescence with CS (17).…”
Section: Discussionmentioning
confidence: 99%
“…CS is described as a cluster of symptoms as part of an underlying disorder, mostly depressive and bipolar (15)(16)(17)(18). Although our initial diagnosis was major depressive disorder with psychotic features, patients must be followed closely for bipolar disorder because of manic symptoms after treatment with escitalopram, and an increased risk of bipolar disorder during adolescence with CS (17). The most frequent symptoms of CS are depressive mood (89%), nihilistic delusions concerning one's own body (86%), nihilistic delusions concerning one's own existence (69%), anxiety (65%), delusions of guilt (63%), delusions of immortality (55%), and hypochondriac delusions (58%) (19).…”
Section: Discussionmentioning
confidence: 99%
“…This is a rare syndrome and till today prevalence and incidence is not known 3 .This syndrome is usually encountered in middle aged or older people with more commonly affecting females 4 . Cotard's syndrome is seen most commonly with severe major depressive patients 5 ,but also occur with various psycho-organic conditions like Schizophrenia 6 , Bipolar disorders 7 , depersonalisation disorder 8, dementia 9 ,temporal lobe epilepsy 10 , parkinson's disease 11 ,brain injury 12 .We report a case of cotard's delusion in bipolar disorder type-II who presented with self destructive behaviour in the form of self starvation leading to sudden collapse.…”
Section: Introductionmentioning
confidence: 91%